Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Evaluate the function [tex]f(x) = x^2 - 2x - 5[/tex] at the given values of the independent variable and simplify.

a. [tex]f(-7)[/tex]

b. [tex]f(x+7)[/tex]

c. [tex]f(-x)[/tex]


Sagot :

Let's evaluate the function [tex]\( f(x) = x^2 - 2x - 5 \)[/tex] at the given values and simplify the expressions step-by-step.

### Part (a): Evaluate [tex]\( f(-7) \)[/tex]

To find [tex]\( f(-7) \)[/tex], we substitute [tex]\( x = -7 \)[/tex] into the function:

[tex]\[ f(-7) = (-7)^2 - 2(-7) - 5 \][/tex]

Simplify each term:

- [tex]\((-7)^2 = 49\)[/tex]
- [tex]\(-2(-7) = 14\)[/tex]
- [tex]\(-5\)[/tex] remains [tex]\(-5\)[/tex]

Combine these results:

[tex]\[ f(-7) = 49 + 14 - 5 = 63 - 5 = 58 \][/tex]

So,

[tex]\[ f(-7) = 58 \][/tex]

### Part (b): Evaluate [tex]\( f(x+7) \)[/tex]

To find [tex]\( f(x+7) \)[/tex], we substitute [tex]\( x = x+7 \)[/tex] into the function:

[tex]\[ f(x+7) = (x+7)^2 - 2(x+7) - 5 \][/tex]

First, expand [tex]\( (x+7)^2 \)[/tex]:

[tex]\[ (x+7)^2 = x^2 + 14x + 49 \][/tex]

Next, distribute [tex]\(-2\)[/tex] to [tex]\((x+7)\)[/tex]:

[tex]\[ -2(x+7) = -2x - 14 \][/tex]

Combine all these terms:

[tex]\[ f(x+7) = x^2 + 14x + 49 - 2x - 14 - 5 \][/tex]

Simplify by combining like terms:

[tex]\[ f(x+7) = x^2 + (14x - 2x) + (49 - 14 - 5) = x^2 + 12x + 30 \][/tex]

Thus,

[tex]\[ f(x+7) = x^2 + 12x + 30 \][/tex]

### Part (c): Evaluate [tex]\( f(-x) \)[/tex]

To find [tex]\( f(-x) \)[/tex], we substitute [tex]\( x = -x \)[/tex] into the function:

[tex]\[ f(-x) = (-x)^2 - 2(-x) - 5 \][/tex]

Simplify each term:

- [tex]\((-x)^2 = x^2\)[/tex]
- [tex]\(-2(-x) = 2x\)[/tex]
- [tex]\(-5\)[/tex] remains [tex]\(-5\)[/tex]

Combine these results:

[tex]\[ f(-x) = x^2 + 2x - 5 \][/tex]

Thus,

[tex]\[ f(-x) = x^2 + 2x - 5 \][/tex]

### Summary:

a. [tex]\( f(-7) = 58 \)[/tex]

b. [tex]\( f(x+7) = x^2 + 12x + 30 \)[/tex]

c. [tex]\( f(-x) = x^2 + 2x - 5 \)[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.